Evaluation Of It System Operational Services Using The Itil Framework In The Service Desk Domain (A Case Study Of PT Erafone Dotcom) - Restamauli br Nainggolan; Budi Tjahjono; Agung Mulyo Widodo; Habibullah Akbar (Eduvest - Journal of Universal Studies, 2025)
PT Erafone dotcom is one of the mobile phone and tablet retailer companies in Indonesia from various well-known brands. PT Erafone dotcom uses the service desk as an after-sales support system service for customers or users in the smooth transaction process. The current problem with service desk services is the slow response to handling and resolving obstacles. Evaluation is needed to be able to improve operational services. The Information Technology Infrastructure Library (ITIL) V4 will be used to evaluate service desk services in IT Operational at PT Erafone Dotcom. The purpose of this study is to evaluate IT Support in operational services using the ITIL V4 framework with 2 practices in the domain of General Management Practice and 5 practices in the domain of Service Management Practice. The results of this study are that the level of service in IT Operational and the level of capability are at level 3 (Defined), which means that IT Operational support to users has run optimally referring to management practice procedures and response to incidents. To increase the value of IT Operational support from the maturity level to match expectations and can improve management. The recommendation for improvement is that even though it is at level 3, there is still a gap in the practices used so that it is necessary to improve the recording of incidents and problems that occur, so that they can be analyzed and identified to help handle and prevent the recurrence of incidents and problems.